Relação profissional-paciente em oncologia: perspectiva de enfermeiros sobre os "pacientes difíceis" - Selbach, Lenise (2023)
Illness from cancer commonly involves long and cyclical treatments, in which close affective relationships are established between patients and professionals. In some situations and for reasons not always conscious to professionals, some patients are considered “difficult”. In view of this, conflicting relationships can be established, with negative impacts on the treatment process, as well as on the health of professionals and patients. Thus, this clinical-qualitative, descriptive and exploratory study was developed with the general objective of understanding how nurses perceive the relationship with cancer patients considered “difficult”. The study included nursing professionals, of both sexes, who worked for at least one year in the adult oncohematology sector and excluded from the study professionals who were away from their function in the period, totaling eight participants. It is noteworthy that the study was approved by the Research Ethics Committee of the Federal University of Santa Maria, under CAAE 54909721.3.0000.5346 and followed all the assumptions of the legislation involving research with human beings. Data collection took place between March/2022 and August/2022, through eight rounds of participant observation, recorded in a Field Diary and eight semi-structured interviews carried out individually, which were recorded and transcribed verbatim. For the analysis of the information, Turato's Clinical-Qualitative Content Analysis was used, and the Nvivo® software was used. To present the results, three articles were prepared, one theoretical and two empirical. Participants named as “difficult” patients and family members who showed aggressive behavior, requested the team excessively, did not adhere to treatment or were considered negligent with their health. Empathetic listening was considered as a resource that makes it possible to broaden the perspectives of evaluation and manage the situation. However, this is not always possible, and in some cases, professionals may react aggressively, or develop a detachment posture, in an attempt to avoid conflicts. In this sense, it is considered that “difficult” relationships occur, which need understanding and care, so that resources that facilitate these interactions are developed. In view of this, the importance of investing in actions that allow professionals to know and identify their own reactions to patients is highlighted, which can favor and improve care strategies. As this is a study carried out in a specific and restricted context, it is considered important that new studies be carried out in different contexts and with greater variability of the public in order to broaden the discussions on the subject.